Anísio Teixeira, a Leader of Brazilian Education: Why is His Legacy Ignored Today? - Almeida-Filho, Naomar; Bruno-Jofré, Rosa (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2022)
The article discusses Aníseio Teixeira’s role in Brazilian education. It makes the point that conservative restorations impeded Teixeira’s innovations from taking root. This situation explains why his legacy was largely moved to oblivion. Of relevance here is the influence of John Dewey’s writings on Teixeira’s conceptions of education and his reading of Dewey’s theoretical and conceptual framework. The authors put emphasis on his understanding of university reform, his institutional experiment at the University of the Federal District and University of Brasilia. They further attempt to explain why his legacy is ignored today. The article goes to the “long 1960s” to refer to the historical conjuncture and the emergence of Paulo Freire’s pedagogy as an epistemological break that led to a reconstruction of the notion of political subject, becoming an inspiration to those envisioning a different social order. This left Teixeira in the historical background.